Women's labour supply and household insurance in Africa - Sonia Bhalotra; Marcela Uma\~na-Aponte (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2012)
This paper investigates whether cyclical variation in women's labour supply in Africa contributes to smoothing household consumption. We find little support for this hypothesis. Using comparable individual data on about 0.5 million women in 30 Sub-Saharan African countries merged with country level panel data on GDP during 1987-2006, we find that the within-country relationship of women's employment and income is, on average, positive. This finding is robust to controls for country-specific trends and potentially correlated shocks. Examination of business cycle variation in the distribution of women's employment across sectors suggests that recessions are associated with increases in unemployment and self-employment relative to paid employment. The results have potentially important implications for understanding coping mechanisms, labour markets, fertility timing, and investments in children.
Keywords: J22; J13; 330; insurance; women's labour supply; added worker effect; business cycles; Africa; Weibliche Arbeitskräfte; Arbeitsangebot; Haushaltsökonomik; Konjunktur; Afrika südlich der Sahara